Spinal Seeding Metastasis of Myxopapillary Ependymoma: Report of Three Pediatric Patients and a Brief Literature Review - Abdallah, Anas (My University, 2020)
Objective:Myxopapillary ependymomas (MPEs) in children are rarely reported low-grade glial tumors; however, MPEs sometimes possess malignant characteristics such as spinal seeding/drop metastasis (SSM). We aimed to present 3 pediatric MPE cases that experienced SSM at 2 neurosurgical centers.Materials and Methods:We retrospectively reviewed the medical records of 38 primary spinal MPE cases who underwent surgery at 2 neurosurgical centers spanning 16 years, from 2004 to 2019. All pediatric cases (patient age <18 years) who were diagnosed with MPE and re-presented with SSM were selected as the core sample for this study. Relevant literature was briefly reviewed.Results:Three pediatric MPE cases (2 females and 1 male) experienced SSM. The mean age at first presentation was 12.0 +/- 1.0 years. The mean preoperative course was 2.9 +/- 1.2 months. The predominant location was the lumbar spine in 2 tumors (both originated from terminal filum [TF]). Two tumors were located intradural intramedullary. Gross-total resection was achieved in 2 patients. No patient had neurofibromatosis type 2. No adjuvant treatment was given after the first surgery. The mean period between the first diagnosis and diagnosis of SSM was 44.0 +/- 31.5 months. The location of SSM in all patients was the sacral spine (1 patient experienced distant metastasis in her brain besides her sacral metastasis). The mean follow-up was 68.3 +/- 53.7 months.Conclusions:We found a statistically significant relationship between SSM in pediatric MPEs and the intramedullary location, TF origin, and number of affected segments. Close clinical and radiological follow-up is essential for pediatric MPE patients.